PEMBERIAN MEREK DAN PENERAPAN PEMASARAN MENGGUNAKAN MEDIA SOSIAL SEBAGAI STRATEGI PEMASARAN PRODUK BERAS DI WILAYAH CIAWI KABUPATEN TASIKMALAYA - Depy Muhamad Pauzy; Gian Riksa Wibawa; Arif Arif (Universitas Majalengka, 2023)
UMKM Rice in the Ciawi region has the potential to be able to develop their business. Branding and use of social media is now a potential aspect of marketing. This assistance is expected to be able to increase the competitiveness of rice MSMEs and maximize sales. The method in this service is by counseling and discussing material. The results of the dedication that has been carried out are that MSME actors understand the use of social media and the creation of a rice brand as a marketing strategy.